The Cognition of Sensory-Motor and Its Correlation to Some of Physical Fitness Elements and Skill Traits for the Player's Epee - Mohamed Abdulrahman Mohamed (Journal of Global Pharma Technology, 2016)
The game of fencing with the epee passed through a great development in the performance of skill and plan through the increased attention given to it by specialists and interested of trainers and researchers, as well as conducting research and studies that have a major role. In upgrading the game for the better. The importance of this research is evidenced by the linking of skills to some sensory abilities - the movement and the elements of physical fitness and motor skills may help in obtaining factors that contribute to the development of learning and training development of the game of fencing with many aspects of epee, hence, the researcher noted that many of the trainers focus in their training on the elements of fitness and motor skills without taking into account the importance of cognitive abilities - sense of movement and its relationship to these elements and skills played by the player in the stadium. And the relationship between some cognitive abilities of the sense of movement and some elements of fitness and skill qualities of the game of fencing with the epee. The sample of the research was chosen in a deliberate manner, the number of (24) players representing the clubs of Baghdad and the provinces of the game of duel with epee, (4) players for each club and the researcher used the statistical bag for social sciences (SPSS) to address the findings. The most important conclusion was the weakness of the accuracy of the stab, which indicates the weakness of the sense of precision of the weapon (tool) to the legal targets of the competitor. The researcher recommended emphasizing the development of training programs that work on the development and development of flexibility and agility and speed of movement of motorists fencing with epee.Keywords: Cognition, Kinetic sensation, Physical fitness and epee.